Ureteral injuries during different types of hysterecomy: A 7-year series at a single university center. (June 2018) - Barbic, Matija; Telenta, Kalina; Noventa, Marco; Blaganje, Mija
Abstract: Objectives: Accidental ureteral injury with gynaecologic surgery, especially hysterectomy, represents a high risk of patient morbidity. The incidence may vary from centre to centre. As the introduction of new minimally invasive surgical techniques and instruments may have affected the incidence of ureteral injury, we de novo analysed the incidence data for the last seven years. Study design: Incidence of ureteral injury was analysed stratifying the data according to the type of hysterectomy (n = 3071). The incidence rate was reported as a confidence interval (CI). Ureteral injuries were classified as direct or indirect. Results: Fifteen ureteral injuries were registered. The highest incidence was evidenced for radical hysterectomy (CI: 0.82–3.99), followed by laparoscopic radical hysterectomy (CI: 0–11.9). The incidence of direct ureteral injury was 26.6%, half of which were identified during the operative procedure. In 26.7% of the operations resulting in ureteral injury, heat-generating instruments were used. Conclusions: The incidence of ureteral injury during different types of hysterectomy was low. The majority of injuries were indirect. These were injuries which resulted from a micro-trauma, and developed due to the delayed necrosis of the ureteral wall. Laparoscopic approach to radical and simple hysterectomy didn't substantially raise the incidence of ureteral injury.